Influence of different altitudes on productive and reproductive performance of pigs - ZELIANG, ANGAULE KHATE; SHARMA, V B; VIDYARTHI, V K (The Indian Journal of Animal Sciences, 2016)
Upgraded (Hampshire × Indigenous, 270) pigs were distributed to 9 families each in 10 villages situated at different altitudes in Nagaland with 1 male and 2 female pigs/family. Significant higher body weight was recorded at high altitudes, i.e. Porba, Chare and Kohima villages as compared to foothills villages like Murise. Average litter size and weight at birth and weaning were 7.65, 5.17, 5.99 and 10.13 kg, respectively, with furrowing of 60%. Minimum and maximum age at sexual maturity and age at first conception ranged between 7.51 to 7.89 and 8.65 to 9.00 months, respectively. The age at first furrowing and gestation period ranged from 12.48 to 12.77 months and 114 to 117 days, respectively. It can be concluded that body weight gain, litter size and weight at birth and weaning, age at sexual maturity, first conception and gestation period were within the normal range at various altitudes but higher than the indigenous pigs.